Religious System in the Mughal Empire during the Period of Shah Jahan and Aurangzeb - Muhammad Nasihudin Ali (International Journal Ihya' 'Ulum al-Din, 2023)
The advice of the Mughal was established by Zahiruddin Muhammad Babur when he succeeded in defeating Abraham Lodi in the battle of Panipat. It also managed to expose the influence of Islam on the Children of Benua India to becoming wider and then continued by its followers. This research aims to analyze the conditions of Mughal society at the time of Sultan Shah Jahan and Aurangzeb implementing their policies in the community, especially religion. This is done because the Indian Subcontinent is an area whose people are Hindu. The method used is library research. This is done to answer the main research question, achieve the study's purpose, and have relevance to the technique used. The method facilitates research by providing insight into Sultan Shah Jahan's and Aurangzeb's policies. In his politics, Shah Jahan tolerated his Hindu people in his activities. They are also assured of their security as citizens of their religion. Moreover, when Aurangzeb did not find a place in the synagogue to be a part of the synagogue, Aurangzeb was more pressed on the values of Islamic society.